Piriformospora indica reduces fusarium head blight disease severity and mycotoxin DON contamination in wheat under UK weather conditions. (11th December 2015) - Rabiey, M.; Shaw, M. W.
Abstract : Piriformospora indica (Sebacinaceae) is a cultivable root endophytic fungus. It colonizes the roots of a wide range of host plants. In many settings colonization promotes host growth, increases yield and protects the host from fungal diseases. Evaluation was made of the effect of P. indica on fusarium head blight (FHB) disease of winter (cv. Battalion) and spring (cv. Paragon, Mulika, Zircon, Granary, KWS Willow and KWS Kilburn) wheat and consequent contamination by the mycotoxin deoxynivalenol (DON) under UK weather conditions. Interactions of P. indica with an arbuscular mycorrhizal fungus ( Funneliformis mosseae ), fungicide application (Aviator Xpro) and low and high fertilizer levels were considered. Piriformospora indica application reduced FHB disease severity and incidence by 70%. It decreased mycotoxin DON concentration of winter and spring wheat samples by 70 and 80%, respectively. Piriformospora indica also increased aboveground biomass, 1000‐grain weight and total grain weight. Piriformospora indica reduced disease severity and increased yield in both high and low fertilizer levels. The effect of P. indica was compatible with F. mosseae and foliar fungicide application. Piriformospora indica did not have any effects on plant tissue nutrients. These results suggest that P. indica might be useful in biological control of Fusarium diseases of wheat.